Association of Single-Nucleotide Variants in ACE2 with the Persistence of Positive qPCR Test for SARS-CoV-2 in Healthcare Professionals During the First Wave of the COVID-19 Pandemic - Karina Jiménez-Gil; Jorge Alberto Cerón-Albarrán; Melissa Daniella Gonzalez-Fernandez; Rosalba Sevilla-Montoya; Alberto Hidalgo-Bravo; Javier Angeles-Martínez; Daniel Montes-Herrera; Oscar Villavicencio-Carrisoza; Carmen Selene García-Romero; José Esteban Muñoz-Medina; Irma Eloisa Monroy-Muñoz (Microorganisms)
The persistence of qPCR positivity for SARS-CoV-2 in individuals who recovered from COVID-19 raised several questions regarding viral transmission, with a special interest in healthcare professionals who may pose a risk of transmitting SARS-CoV-2. This issue highlights the necessity for identifying the genetic risk factors associated with persistent SARS-CoV-2 infection. A promising target for achieving this goal is the angiotensin-converting enzyme 2 (ACE2) gene, which has been associated with clinical characteristics of COVID-19 infection, such as severity. The analysis of samples from the first wave of the COVID-19 pandemic represents the initial response of the immune human system against this new virus, without the effect of vaccination or the presence of multiple strains. The aim of this study was to analyze the association of genetic variants in ACE2 with persistent SARS-CoV-2 infection. We conducted a case–control study, including 151 healthcare workers who tested positive for SARS-CoV-2 by qPCR during the first wave of the COVID-19 pandemic, and who were followed up until their results were negative. ACE2 was sequenced through Sanger sequencing. The sequence was compared against a reference sequence and variants identified. Four ACE2 variants were associated with persistent SARS-CoV-2 qPCR positivity. Three of the variants with an effect on the resulting protein were associated with increased risk of persistent SARS-CoV-2 qPCR positivity, NG_012575.2:g.35481 C>T, NG_012575.2:g.35483 G>T and NG_012575.2:g.35498 G>T. On the other hand, the rs2285666 (NG_012575.2:g.14934 G>A) was associated with a higher risk for persistent SARS-CoV-2 qPCR positivity in women and rs4646150 (NG_012575.2:g.25701 G>A) in men. The NG_012575.2:g.35498 G>T variant represents an amino acid change with a possibly harmful effect on ACE2 function. Our results suggest that ACE2 variants might be useful for identifying the population at higher risk for developing persistent SARS-CoV-2-positive qPCR results. This knowledge can be helpful for designing health policies for protecting healthcare professionals and, in consequence, users of health services.